METHODICAL APPROACHES TO STRUCTURING EDUCATIONAL MATERIAL BY MULTIMEDIA IN THE PROCESS OF TRAINING FUTURE SPECIALISTS ECONOMIC PROFILE (Pedagogy of Higher and Secondary Education, 2007)
The article observes the matters of structuring the learning materials, and projecting the strategy of realization of learning process that is accomplished using certain combinations of didactic components of multimedia learning software means.